(untitled) (Al-Aasar, 2025)
Islam’s special feature is that it gives importance to law and ethics together. Law without ethics is useless, and ethics without law are incomplete. In every age, the Prophet ﷺ taught sciences and beliefs along with moral education and purification of the heart. This applies both to personal life and to society. The Prophet ﷺ spent both times—one with knowledge and the other with worship—simultaneously. The reality is that history is completed by following the perfect instructions given by a commander like the Prophet ﷺ, and every benefit and historical text is preserved in this way. The first Islamic treaty (known as the Kitab = Covenant) was the agreement made by the Prophet Muhammad ﷺ with the Christians and Jews of Arabia. In this treaty, believers were given protection and rights, and the youth of all nations were included in the agreement so that they could participate in society and war together. In the pre-Islamic era, people were divided into separate nations and tribes. After accepting Islam, these divisions were removed and replaced by a unified community. The killing of innocent blood was considered harmful and forbidden, and instead, collective protection and family responsibility were emphasized. Islam brought people together under one belief and made them a united nation. The ultimate goal of Islam is to establish a nation based on faith and righteous conduct, not just personal desires.